Vaccination With Leptospira interrogans PF07598 Gene Family-Encoded Virulence Modifying Proteins Protects Mice From Severe Leptospirosis and Reduces Bacterial Load in the Liver and Kidney - Chaurasia, Reetika; Salovey, Aryeh; Guo, Xiaojia; Desir, Gary; Vinetz, Joseph M. (Frontiers in Cellular and Infection Microbiology, 2022)
The molecular and cellular pathogenesis of leptospirosis remains poorly understood. Based on comparative bacterial genomics data, we recently identified the hypothetical PF07598 gene family as encoding secreted exotoxins (VM proteins) that mediate cytotoxicity in vitro. To address whether VM proteins mediate in vivo leptospirosis pathogenesis, we tested the hypothesis that VM protein immunization of mice would protect against lethal challenge infection and reduce bacterial load in key target organs. C3H/HeJ mice were immunized with recombinant E. coli-produced, endotoxin-free, leptospiral VM proteins (derived from L. interrogans serovar Lai) in combination with the human-compatible adjuvant, glucopyranoside lipid A/squalene oil-in-water. Mice receiving full length recombinant VM proteins were protected from lethal challenge infection by L. interrogans serovar Canicola and had a 3-4 log10 reduction in bacterial load in the liver and kidney. These experiments show that immunization with recombinant VM proteins prevents leptospirosis clinical pathogenesis and leads to markedly reduced key target organ infection in this animal model. These data support the role of leptospiral VM proteins as virulence factors and suggest the possibility that a VM protein-based, serovar-independent, pan-leptospirosis vaccine may be feasible.